Clinical Characteristics and Management of Patients With McCune-Albright Syndrome With GH Excess and Precocious Puberty: A Case Series and Literature Review - Zhai, Xiao; Duan, Lian; Yao, Yong; Xing, Bing; Deng, Kan; Wang, Linjie; Feng, Feng; Liang, Zhiyong; You, Hui; Yang, Hongbo; Lu, Lin; Chen, Shi; et al. (Frontiers in Endocrinology, 2021)
Background: Fibrous dysplasia/McCune-Albright syndrome is a rare disorder characterized by fibrous dysplasia, café au lait skin spots, and hyperfunctioning endocrinopathies. Coexistence of precocious puberty and growth hormone excess in fibrous dysplasia/McCune-Albright syndrome is a rare condition. Both conditions can manifest accelerated growth, and treatments can be more challenging for such patients. The objective was to describe the clinical manifestations of combined GH excess and PP in the context of fibrous dysplasia/McCune-Albright syndrome, and analyze the predicted adult height or final height in these patients. Method: Clinical data from 60 fibrous dysplasia/McCune-Albright syndrome patients from Peking Union Medical College Hospital were obtained, and published studies and case reports were systemically searched. Demographic characteristics, GH, IGF-1, prolactin , ALP, and sex hormone level, growth velocity, and bone age data were obtained. The GV Z-score, bone age over chronological age ratio and predicted adult height Z-score were calculated before and after treatment. Results: We reviewed 7 patients from Peking Union Medical College Hospital (5 females) and 39 patients (25 females) from published literature. Six out of the 7 patients from Peking Union Medical College Hospital and half of the patients from published studies were pediatric patients. These pediatric patients had increased growth velocity Z-score and bone age over chronological age ratio. After good control of both conditions, the growth velocity Z-score and bone age over chronological age ratio decreased significantly, and the predicted adult height Z-score increased. The final heights and predicted adult height Z-scores were not impaired in patients who had gigantism. All of the patients had craniofacial fibrous dysplasia associated with optic and otologic complications. Conclusion: Fibrous dysplasia/McCune-Albright syndrome with growth hormone excess and precocious puberty is more common in girls. Patients have accelerated linear growth and advanced skeletal age, and early and good control of both conditions leads to reduced growth velocity and stabilized bone age. The predicted adult height and final height are not negatively affected when growth hormone excess is diagnosed in pediatric patients.